2001
DOI: 10.1029/2000gl011788
|View full text |Cite
|
Sign up to set email alerts
|

Subglacial sediments: A regional geological template for ice flow in West Antarctica

Abstract: Abstract. We use aerogeophysical data to estimate the distribution of marine subglacial sediments and fault-bounded sedimentary basins beneath the West Antarctic Ice Sheet (WAIS). We find that significant ice flow occurs exclusively in regions covered by subglacial sediments. The onsets and lateral margins of ice streams coincide with the limit of marine sediments. Lateral margins are also consistently linked with fault-bounded basins. We predict that the inland migration of ice streams B and Cx towards the ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
132
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 16 publications
5
132
0
Order By: Relevance
“…In PD09 it was twovalued, depending on whether the modern rebounded Antarctic bedrock is above or below sea level: if above, C(x, y)=10 −10 m a −1 Pa −2 representing hard bedrock (mainly EAIS), and if below, C(x, y) = 10 −6 m a −1 Pa −2 representing deformable sediment (mainly WAIS) (e.g., Studinger et al, 2001) shown in Fig. 3a.…”
Section: Basal Sliding Coefficientsmentioning
confidence: 99%
“…In PD09 it was twovalued, depending on whether the modern rebounded Antarctic bedrock is above or below sea level: if above, C(x, y)=10 −10 m a −1 Pa −2 representing hard bedrock (mainly EAIS), and if below, C(x, y) = 10 −6 m a −1 Pa −2 representing deformable sediment (mainly WAIS) (e.g., Studinger et al, 2001) shown in Fig. 3a.…”
Section: Basal Sliding Coefficientsmentioning
confidence: 99%
“…Subglacial geology (e.g. the presence of deformable till) also influences the position of ice-stream margins (Anandakrishnan and others, 1998;Bell and others, 1998; Blankenship and others, 2001; Studinger and others, 2001). Most of Thwaites Glacier's tributaries clearly originate within bedrock troughs (Holt and others, 2006; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[7] It is uncertain whether similar mechanisms act in the EAIS, because unlike the WAIS, most of East Antarctica is not grounded below sea level and so marine sediments may not be as widespread Blankenship et al, 1986;Joughin et al, 1999;Studinger et al, 2001]. Studies of East Antarctic ice dynamics are currently extremely under-represented in the literature, and there has been no investigation of the controls on enhanced flow here.…”
mentioning
confidence: 99%
“…From calculations of isostatically adjusted topography, it has been suggested that marine sediments, deposited before the formation of the West Antarctic Ice Sheet (WAIS), and during periods when the ice sheet collapsed, may be widespread in the Siple Coast region [Scherer et al, 1998;Studinger et al, 2001]. Additionally, aerogeophysical and seismic data from the tributaries of Ice Stream C and Whillans Ice Stream on the Siple Coast, have indicated that enhanced flow tributaries coincide well with sedimentary basins [Anandakrishnan et al, 1998;Bell et al, 1998;Blankenship et al, 2001;Studinger et al, 2001].…”
mentioning
confidence: 99%
See 1 more Smart Citation